KAJIAN ASPEK EKOLOGIS DAN DAYA DUKUNG PERAIRAN SITU CILALA - Pratiwi, Niken T.M.; Hariyadi, Sigid; Ayu, Inna Puspa; Iswantari, Aliati; MZ, Novita; Apriadi, Tri (JURNAL BIOLOGI INDONESIA, 2015)
ABSTRACTEcological aspect (morphometry, a complexity of community structure, trophic state, and carrying capacity) are one of basic information to build comprehensive management concept of aquatic ecosystem, as Lake Cilala.  The concept was addressed to develop ornamental fish floating cage and natural fishery activity.  Lake Cilala is a longwise shape small lake with maximum length, average width, and average depth as 1141 m, 161 m, 2.67 m respectively.  Lake Cilala has various genera of phytoplankton and zooplankton, 8 genera of benthos, 5 genera of aquatic plants, and 12 fish species including planktivore, herbivore, and carnivore fishes.  Those organisms established food chains, by grazing and detritus food chain.  The trophic state of Lake Cilala was categorized as middle to heavy eutrophic level by Trophic State Index (TSI).  The carrying capacity analysis of Lake Cilala is 130 tons/year. It is resulted a possibility to increase ornamental fish floating cage to 165 units from 300 existed units. Furthermore, the carrying capacity for natural fish was reached 3.77 tons/year. Keywords: carrying capacity, food chain, lake fisheries, small lake management, trophic state